Measurement of Mathematical expression correlations at the CERN Mathematical expression collider - Albajar,C; Ankoviak,K; Bartha,S; Bezaguet,A; Böhrer,A; Bos,K; Buchanan,C; Buschbeck,B; Castilla-Valdez,H; Cennini,P; Cittolin,S; Clayton,E; et al. (Zeitschrift Fur Physik C Particles and Fields, 1994)
We report on measurements of correlated Mathematical expression production in Mathematical expression collisions at Mathematical expression, using dimuon data to tag both the b and Mathematical expression quarks. Starting from an inclusive dimuon sample we obtain improved cross-sections for single inclusive beauty production and confirm our earlier results on Mathematical expression mixing. From a study of Mathematical expression correlations we derive explicit cross-sections for semi-differential Mathematical expression production. We compare the measured cross-sections and correlations to Mathematical expression QCD predictions and find good quantitative agreement. From the measured angular distributions we establish a size-able contribution from higher order QCD processes with a significance of about seven standard deviations. A large nonperturbative contribution to these higher order corrections is excluded. © 1994 Springer-Verlag.